PENGARUH SUKU BUNGA, KEPUASAN NASABAH, DAN KUALITAS LAYANAN TERHADAP LAYANAN LOYALITAS NASABAH BANK SYARIAH - Sriyono, Sriyono; Rofila, Jihan (Media Mahardhika, 2024)
This research aims to test and determine the influence of interest rates, customer satisfaction and service quality on sharia bank customer loyalty services. The type of research used is quantitative. The population and sample in this research are Sharia Bank customers in Indonesia. The sampling technique used was a Likert scale using a saturated sampling technique, so that 100 respondents were obtained. The way to collect data is by distributing questionnaires to respondents who are customers of Sharia Banks in Indonesia. The analytical method used is the data analysis technique used is the classical assumption test and multiple linear regression analysis. The classic assumption test consists of a normality test and a multicollinearity test using the SPSS application. The research results show that (1) interest rates have a positive and significant effect on customer loyalty services, (2) partial customer satisfaction has no effect on customer loyalty services, (3) service quality has a positive and significant effect on customer loyalty services (4) interest rates, customer satisfaction and service quality simultaneously have a positive influence on customer loyalty services of sharia banks in Indonesia.